Correlation of Influenza B Haemagglutination Inhibiton, Single-Radial Haemolysis and Pseudotype-Based Microneutralisation Assays for Immunogenicity Testing of Seasonal Vaccines - Carnell, George W. (Vaccines (Basel), 2021)
Influenza B is responsible for a significant proportion of the global morbidity, mortality and economic loss caused by influenza-related disease. Two antigenically distinct lineages co-circulate worldwide, often resulting in mismatches in vaccine coverage when vaccine predictions fail. There are currently operational issues with gold standard serological assays for influenza B, such as lack of sensitivity and requirement for specific antigen treatment. This study encompasses the gold standard assays with the more recent Pseudotype-based Microneutralisation assay in order to study comparative serological outcomes. Haemagglutination Inhibition, Single Radial Haemolysis and Pseudotype-based Microneutralisation correlated strongly for strains in the Yamagata lineage; however, it correlated with neither gold standard assays for the Victoria lineage.